2012
DOI: 10.1517/14656566.2012.652085
|View full text |Cite
|
Sign up to set email alerts
|

Paroxetine for the treatment of depression: a critical update

Abstract: In previous subanalysis and metaregression analysis, paroxetine failed to show clear differences in terms of efficacy across clinical subgroups. Thus, nowadays the pharmacokinetic and pharmacodynamic properties of the molecule are fundamental to guiding its prescription, both for efficacy and tolerability issues, for example, it can have a high impact on sexual function and weight should also be considered at the beginning of treatment. Since prescription is still based mainly on its side-effect profile, newer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(14 citation statements)
references
References 90 publications
1
13
0
Order By: Relevance
“…A review of tolerability based on data from randomized controlled clinical trials involving about 4000 patients with short-term and long-term treatments indicated that paroxetine was associated with significantly higher incidence of adverse events related to sexual dysfunction, as well as more discontinuation symptoms, than escitalopram (Baldwin et al , 2007b). In general, these findings are consistent with a recent review on the overall profile of paroxetine (Gibiino and Serretti, 2012). …”
Section: Clinical Efficacy and Tolerabilitysupporting
confidence: 92%
“…A review of tolerability based on data from randomized controlled clinical trials involving about 4000 patients with short-term and long-term treatments indicated that paroxetine was associated with significantly higher incidence of adverse events related to sexual dysfunction, as well as more discontinuation symptoms, than escitalopram (Baldwin et al , 2007b). In general, these findings are consistent with a recent review on the overall profile of paroxetine (Gibiino and Serretti, 2012). …”
Section: Clinical Efficacy and Tolerabilitysupporting
confidence: 92%
“…Paroxetine is approved and marketed for use in treating patients with a number of depression- and anxiety-related disorders (30, 31). A wealth of data is available from clinical trials and postclinical application regarding human bioavailability, toxicity, adverse effects, and contraindications.…”
Section: Discussionmentioning
confidence: 99%
“…Paroxetine is a selective serotonin reuptake inhibitor that is widely used in the treatment of mental disorders, including depression, panic disorders, and obsessive compulsive disorder 1. Two previous studies suggested that the plasma drug con centration is associated with the therapeutic response to paroxetine 2,3.…”
Section: Introductionmentioning
confidence: 99%